Policy-Induced Environmental Technology and Inventive Efforts: Is There a Crowding Out? - Hanna Hottenrott; Sascha Rexhäuser (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Significant policy effort is devoted to stimulate the development, adoption and diffusion of environmental-friendly technology. Sceptics worry about the effects of regulation-induced environmental technology on firms competitiveness. Since innovation is a crucial productivity driver, a potential crowding out of inventive efforts could increase the cost of mitigating environmental damage. Using propensity score matching, we study the short-term effects of regulation-induced environmental technology on non-green innovative activities for a sample of firms in Germany. We find indeed some evidence for a crowding out of the firms R&D and total innovation expenditures net of those costs due to the environmental innovation. The estimated treatment effect is larger for firms that are likely to face financing constraints. No significant effects are observed for the number of R&D projects and investments in non-innovation-related assets. Likewise, for firms with subsidy-backed environmental innovations no crowding out is found.
Keywords: O33; O31; Q55; 330